Is there a new reforming spirit at international organisations? The example of UNCTAD IX - Berend Diekmann (Intereconomics, 1996)
When the G7 summit in Lyon discussed the reform of multilateral institutions, the spotlight fell unexpectedly on UNCTAD. The final communiqué stated that UNCTAD IX was a milestone on the road towards the renewal of the organisation. The outcome of the conference was also cited as proof of the effectiveness of G7 initiatives to reform international institutions. Finally, the communiqué went so far as to declare that the reform of UNCTAD was a point of reference (in other words, a model) for the reform of the entire economic and social apparatus of the United Nations. What progress did UNCTAD IX really bring? Is it appropriate to regard UNCTAD IX as a yardstick for the reform of other organisations?
Keywords: 330; UNCTAD